2020
DOI: 10.18775/ijied.1849-7551-7020.2015.61.2001
|View full text |Cite
|
Sign up to set email alerts
|

Insolvency Risk. Application of Altman Z-Score to the Auto Parts Sector in Romania

Abstract: This paper intends to apply the Altman Z-score model to all the companies active in the wholesale of motor vehicle parts and accessories (NACE 4531), with extended financial statements. Using the panel data model over the time series for 2008-2016 on the companies of this sector, we conclude that 99% of the Z-score is explained by the independent variables (working capital, capital structure, turnover, earnings before interest and tax), with estimated parameters very close to the model`s classical values. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…For instance, Numerous researchers (Islam & Fakir, 2023;Puspita et al, 2023;Ramana et al, 2023;Nimbalkar & Marisetty, 2022) have utilized Altman's Z-Score model to forecast financial distress within the cement industry across various countries, yielding diverse research outcomes. Several researchers (Rahman & Acharya, 2022;Sareen & Sharma, 2022;Swalih et al, 2021;Baciu et al, 2020) have applied Altman's Z-Score model to predict financial distress within the automobile industry across different regions, each offering unique insights and findings. Researchers (Goh et al, 2022;Lestari et al, 2021;Lewaru & Loupatty, 2021) have shown considerable interest in using Altman's Z-Score model to assess the financial health of the tourism and hospitality industry in different regions, unveiling a spectrum of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Numerous researchers (Islam & Fakir, 2023;Puspita et al, 2023;Ramana et al, 2023;Nimbalkar & Marisetty, 2022) have utilized Altman's Z-Score model to forecast financial distress within the cement industry across various countries, yielding diverse research outcomes. Several researchers (Rahman & Acharya, 2022;Sareen & Sharma, 2022;Swalih et al, 2021;Baciu et al, 2020) have applied Altman's Z-Score model to predict financial distress within the automobile industry across different regions, each offering unique insights and findings. Researchers (Goh et al, 2022;Lestari et al, 2021;Lewaru & Loupatty, 2021) have shown considerable interest in using Altman's Z-Score model to assess the financial health of the tourism and hospitality industry in different regions, unveiling a spectrum of outcomes.…”
Section: Introductionmentioning
confidence: 99%